2021
DOI: 10.1002/pen.25812
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of cellulose nanocrystals‐organic montmorillonite as hybrid nanofillers for enhancing mechanical, crystallization, and heat‐resistant properties of three‐dimensional printed poly(lactic acid) nanocomposites

Abstract: Cellulose nanocrystals (CNC)‐organic montmorillonite (OMMT) hybrid nanofillers were prepared, and their effects in reinforcing the performance of three‐dimensional (3D) printed poly(lactic acid) (PLA) nanocomposites were studied. The results indicated that the hybrid CNC‐OMMT nanofillers had a synergistic impact on enhancing the mechanical properties of PLA nanocomposites compared to either single nanofillers (CNC or OMMT). The dispersion of CNC‐OMMT in the PLA matrix was not only significantly improved, but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…These results indicated that the hybrid nanofillers greatly enhanced crystallization of the nanocomposites. The main reason for this was that the well-dispersed hybrid nanofillers were efficient heterogeneous-nucleating agents and improved the crystallization rate [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that the hybrid nanofillers greatly enhanced crystallization of the nanocomposites. The main reason for this was that the well-dispersed hybrid nanofillers were efficient heterogeneous-nucleating agents and improved the crystallization rate [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a recently published report, novel CNC-organic montmorillonite (OMMT) hybrid nanoparticles with favorable thermal stability were constructed by electrostatic self-assembly [ 27 ]. Then, the hybrid nanoparticles were incorporated into a PLA matrix to prepare PLA nanocomposites by FFF 3D printing [ 28 ]. We found that the hybrid nanofillers had synergistic enhancement effects on mechanical, crystallization, and heat resistant properties of the nanocomposites due to dramatically improved dispersion of the hybrid nanofillers in the PLA matrix.…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 ] CNC have distinguished their superior characteristics such as a high aspect ratio, a large surface‐area‐to‐volume ratio, higher Young's modulus and tensile strength, good reinforcing ability, better optical transmittance, and liquid crystalline property. [ 29–32 ]…”
Section: Introductionmentioning
confidence: 99%
“…[22] CNC have distinguished their superior characteristics such as a high aspect ratio, a large surface-area-to-volume ratio, higher Young's modulus and tensile strength, good reinforcing ability, better optical transmittance, and liquid crystalline property. [29][30][31][32] Hexagonal boron nitride (h-BN), or simply BN, has a structure similar to graphene. [33] BN has gained widespread attention in recent years due to its amazing mechanical and thermal properties, [34] such as minimal thermal expansion, high-thermal conductivity with highelectrical resistance, [35] and oxidation resistance at extremely high temperatures.…”
mentioning
confidence: 99%
“…[1,2,[6][7][8][9] Therefore, the PLA shows inferior thermal and thermomechanical resistance with respect to synthetic polyolefins and to improve PLA poor properties, natural clay, metal oxides, natural fibers, cellulose, and so forth, have been evaluated as suitable additives. [6][7][8][9][10][11] These additives increase PLA thermal stability, hardness, and rigidity [12][13][14][15][16] ; however, they reduce biodegradation rate. [12,17] PLA degradation depends on its molecular weight, macromolecular architecture, crystallinity degree, morphology, supramolecular structure, and so forth, but also on the surrounding environmental conditions such as moisture/water, oxygen content, pH, temperature, and/or kind and activity of microorganisms.…”
Section: Introductionmentioning
confidence: 99%